EFEITO DE ALTAS TEMPERATURAS SOBRE Diatraea saccharalis (Fab., 1794) E SEUS INIMIGOS NATURAIS - Parra, J. R. P.; Aguilar, J. A. D.; Botelho, P. S. M. (REVISTA DE AGRICULTURA, 2015)
EFEITO DE ALTAS TEMPERATURAS SOBRE Diatraea saccharalis (Fab., 1794) E SEUS INIMIGOS NATURAIS